2014
DOI: 10.4149/neo_2014_049
|View full text |Cite
|
Sign up to set email alerts
|

The PGI-KLF4 pathway regulates self-renewal of glioma stem cells residing in the mesenchymal niches in human gliomas

Abstract: Gliomas display cellular hierarchies with self-renewing tumorigenic glioma stem cells (GSCs) at the apex. The GSC niches function as a regulator of GSC maintenance, however, the exact components of GSC niches that mediate this process are still far from fully defined. Here, we showed that glioma cells with aberrant mesenchymal phenotypes constitute a mesenchymal niche for GSCs. Using patient-derived specimens, we demonstrated that the paracrine PGI signaling, initiated by mesenchymal glioma cells, induces the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…KLF4 also plays crucial roles in maintenance of neural stem cells, and KLF4 deficiency causes impaired neurogenesis in adult mouse brain [30, 31]. KLF4 induced by PGI initiated by mesenchymal glioma cells, induces the self-renewal and tumorigenic potentials of glioma stem cells [32]. These reports and our findings suggest the potential role of KLF4 in glioma.…”
Section: Discussionsupporting
confidence: 61%
“…KLF4 also plays crucial roles in maintenance of neural stem cells, and KLF4 deficiency causes impaired neurogenesis in adult mouse brain [30, 31]. KLF4 induced by PGI initiated by mesenchymal glioma cells, induces the self-renewal and tumorigenic potentials of glioma stem cells [32]. These reports and our findings suggest the potential role of KLF4 in glioma.…”
Section: Discussionsupporting
confidence: 61%
“…Previous study has demonstrated that SOX2, by marking and regulating the functions of skin tumor-initiating cells and CSCs, establishes a continuum between tumor initiation and progression in primary skin tumors [22]. Zhu et al indicated that the paracrine PGI signaling induced the self-renewal and tumorigenic potentials of GSCs through induction of KLF4; treatment of intracranial orthotopic xenografts with shPGI or shKLF4 leads to less lethal potency [38]. Therefore their data suggested that blockade of the PGI-KLF4 pathway might provide a therapeutic strategy against GSC niches.…”
Section: Discussionmentioning
confidence: 98%
“…These findings highlighted the importance of BMI1 in GSCs. Zhu et al (2014) showed that the PGI-KLF4 pathway regulates self-renewal of GSCs in human gliomas, suggesting blockade of the PGI-KLF4 pathway may provide a therapeutic strategy against GSCs. These studies reinforce the importance of deep understanding of GSC markers.…”
Section: Gscs and Their Characteristicsmentioning
confidence: 99%